(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Water is significant endowment of nature to every single living thing. An existence without water can’t be envisioned. The present investigation of drinking water sources of Morena city in Madhya Pradesh for physical analysis and chemical analysis, through faucet water, Hand siphon’s and borewell destinations which incorporates tests for temperature, pH value, total solids, conductivity, Total Dissolved Solid, Chloride, Carbonate Nitrate, Sulfate, Calcium, magnesium, sodium, potassium, alkalinity to the fluoride, acidity, overall hardness, lead.